Surgical Intervention and Prognosis of Intraductal Papillary Mucinous Adenoma in Elderly Patients: A Single Center Retrospective Study - Tianhan Sun; Meilan Liu; Qing Wang; Boyue Jiang; Tong Li; Jianfu Cao; Jinghai Song; Jingyong Xu; Hongyuan Cui (Aging Medicine)
ABSTRACT Objective The incidence of intraductal papillary mucinous neoplasm (IPMN) is rising among elderly patients. This study aims to investigate the clinical features of IPMN in elderly patients (≥ 60 years), analyze risk factors for high‐grade dysplasia (HGD) and invasive cancer (IC), and provide treatment recommendations for elderly patients with IPMN. Methods In this single‐center retrospective case–control study, 58 consecutive elderly patients (≥ 60 years) who underwent IPMN surgery at Beijing Hospital between January 2014 and November 2023 were included. Clinical characteristics across IPMN subtypes were compared, risk factors were analyzed, and the predictive values of the 2017 Fukuoka and 2023 Kyoto guidelines were evaluated. Follow‐up and survival outcomes were also examined. Results The proportion of patients with main‐duct IPMN (MD‐IPMN) and mixed‐type IPMN (MT‐IPMN) who had diabetes was significantly higher than among those with branch‐duct IPMN (BD‐IPMN) (p < 0.05). The average postoperative hospital stay for patients with low‐grade dysplasia (LGD) was 17.7 days (range, 6–53 days), while for patients with HGD/IC, it was 25.5 days (range, 9–90 days), with a statistically significant difference (p < 0.05). Jaundice, elevated CA19‐9, elevated CEA, main duct (MD) > 10 mm, and IPMN subtype were significant predictors of HGD/IC (p < 0.05), with elevated CA19‐9 and IPMN subtype identified as independent risk factors (p < 0.05). The 2023 Kyoto guidelines showed higher sensitivity but lower specificity than the 2017 Fukuoka guidelines for detecting HGD/IC (p < 0.05 for both). There was a statistically significant difference in overall survival between patients with LGD and those with HGD/IC following surgery (p < 0.05), while no significant difference in postoperative survival was observed between HGD/IC patients with and without lymph node metastasis (p > 0.05). Conclusions Surgical resection is recommended for elderly patients with MD‐IPMN or MT‐IPMN combined with elevated CA19‐9. The 2017 Fukuoka guidelines are preferable to the 2023 Kyoto guidelines for managing elderly IPMN patients.